2008
DOI: 10.1093/comjnl/bxm079
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Performance of Mirrored Disk Organizations

Abstract: This is a followup to the 1994 tutorial by Berkeley RAID researchers whose 1988 RAID paper foresaw a revolutionary change in storage industry based on advances in magnetic disk technology, i.e., replacement of large capacity expensive disks with arrays of small capacity inexpensive disks. NAND flash SSDs which use less power, incur very low latency, provide high bandwidth, and are more reliable than HDDs are expected to replace HDDs as their prices drop. Replication in the form of mirrored disks and erasure co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…This mean response time holds if all requests are writes, but simulation results have shown that with interfering read requests the write response time is higher and closer to R max 2 , when the overall ρ remains the same. Performance analyses of RAID1 in normal and degraded mode are given in [16,103]. The performance of LSI RAID with RMW versus Reconstruct Write (RCW) method [94] is given in [107].…”
Section: Raid1 Performance In Normal Modementioning
confidence: 99%
“…This mean response time holds if all requests are writes, but simulation results have shown that with interfering read requests the write response time is higher and closer to R max 2 , when the overall ρ remains the same. Performance analyses of RAID1 in normal and degraded mode are given in [16,103]. The performance of LSI RAID with RMW versus Reconstruct Write (RCW) method [94] is given in [107].…”
Section: Raid1 Performance In Normal Modementioning
confidence: 99%
“…When a disk fails in basic mirroring, the rate of read requests to the surviving disk is doubled. A solution to this problem is to distribute the data of each disk over n > 1 disks so that if a disk fails, the load increase at surviving disks is 1/n [ Thomasian and Xu 2008;Thomasian and Tang 2012]. Clustered RAID5 to attain a similar effect is described later.…”
Section: Appendix I: Raid5 Disk Arraysmentioning
confidence: 99%
“…When one of two disks fails in BM the read load on the surviving disk is doubled. RAID1 configurations with a smaller load increase than BM are described in [23,26]. The Interleaved Declustering (ID) layout, which was implemented in the Teradata DBC/1012 database machine, distributes the contents of each disk evenly on the remaining n − 1 disks of a cluster of n > 2 disks.…”
Section: Raid1 Mirrored Disk Organizationsmentioning
confidence: 99%
“…The Interleaved Declustering (ID) layout, which was implemented in the Teradata DBC/1012 database machine, distributes the contents of each disk evenly on the remaining n − 1 disks of a cluster of n > 2 disks. If a disk fails the increase of read load per disk is n/(n − 1) < 2 [23,26]. ID will yield a more balanced disk load in HDA following a disk failure, but only BM is considered in this study for the sake of brevity.…”
Section: Raid1 Mirrored Disk Organizationsmentioning
confidence: 99%